Template for the laboratory's report of 25-hydroxyvitamin D: recommendations form the Brazilian Society of Clinical Pathology/Laboratory Medicine (SBPC/ML) and the Brazilian Society of Endocrinology and Metabolism (SBEM) - Carlos Eduardo S. Ferreira; Carolina A. Moreira; Leonardo S. Vasconcellos
ABSTRACT The Brazilian Society of Clinical Pathology/Laboratory Medicine (SBPC/ML) and the Brazilian Society of Endocrinology and Metabolism (SBEM) recommend a new template for laboratory reports of 25-hydroxyvitamin D: deficiency < 20 ng/ml; normal values for the general population between 20-60 ng/ml; ideal values for at-risk population between 30-60 ng/ml; e risk of toxicity > 100 ng/ml.